High-temperature wear-resistant self-lubricating boron-doped diamond coating as well as preparation method and application thereof
By depositing Cr base layer, CrxByCz gradient transition layer and B-DLC functional layer with specific structure and element content on the substrate surface, a high-temperature wear-resistant self-lubricating boron-doped diamond coating is formed, and the toughness of DLC coating in high-temperature environment is solved. and thermal stability issues, excellent self-lubricating and wear resistance at high temperatures of 400 to 500°C are achieved.
Patent Information
- Application Number
- CN202411577565.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-06
AI Technical Summary
Pure DLC coatings have poor toughness, poor thermal stability and sensitive tribological properties to temperature changes in high temperature environments, which limit their use in high temperature harsh environments.
By depositing the Cr base layer, the CrxByCz gradient transition layer and the B-DLC functional layer in sequence on the substrate surface, a high-temperature wear-resistant self-lubricating boron-doped diamond coating is formed. The coating has a specific thickness and composition, enhancing its properties at high temperatures.
The coating exhibits excellent self-lubricating and wear resistance under a high temperature atmospheric environment of 400-500°C, significantly improving the lubrication and wear resistance of DLC films at high temperatures, and expanding its application range.
Smart Images

Figure CN119433438A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coating materials, and in particular to a high-temperature wear-resistant self-lubricating boron-doped diamond-like coating and a preparation method and application thereof. Background Art
[0002] Diamond-like carbon (DLC) is a solid lubricating material with high hardness and low friction. It has been widely used in many high-tech fields such as aerospace and automobiles. The unique physical and chemical properties of DLC coatings make it a preferred material for reducing friction and improving the durability of mechanical parts. However, pure DLC coatings have problems such as poor toughness, poor thermal stability, and sensitivity of their tribological properties to temperature changes in practical applications. These problems seriously limit their use in high-temperature and harsh environments. In particular, DLC coatings begin to undergo graphitization transformation when the temperature reaches about 300°C, and this process causes significant degradation of their mechanical and tribological properties. Therefore, it is of great significance to improve the toughness and thermal stability of DLC films and reduce their sensitivity to temperature in order to expand the temperature range for their lubrication application.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] The object of the present invention is to provide a high-temperature wear-resistant self-lubricating boron-doped diamond-like coating and a preparation method and application thereof, so as to solve or improve the above technical problems.
[0005] The present invention can be implemented like this:
[0006] In a first aspect, the present invention provides a high-temperature wear-resistant self-lubricating boron-doped diamond-like coating, wherein the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating comprises a Cr base layer, a Cr x B y C z Gradient transition layer and B-DLC functional layer;
[0007] The Cr base layer has a columnar structure, and the thickness of the Cr base layer is 0.15 μm to 0.25 μm; x B y C z The gradient transition layer has a columnar structure, Cr x B y C z The thickness of the gradient transition layer is 0.05 μm to 0.10 μm; the B-DLC functional layer has a dense featureless structure, and the thickness of the B-DLC functional layer is 0.8 μm to 2.0 μm;
[0008] In the Cr base layer, the mass percentage of Cr is 99.5% to 99.99%; x By C z In the gradient transition layer, the mass percentage of Cr is greater than 0 and does not exceed 99.99%, the mass percentage of B is greater than 0 and does not exceed 8%, and the remainder is C; in the B-DLC functional layer, the mass percentage of B is 3% to 5%, and the remainder is C.
[0009] In an optional embodiment, along the direction from close to the Cr coating layer to away from the Cr coating layer, Cr x B y C z In the gradient transition layer, the mass percentage of Cr gradually decreases from 99.99% to 0, and the mass percentage of B gradually increases from 0 to 8%.
[0010] In an optional embodiment, the high temperature wear-resistant self-lubricating boron-doped diamond-like coating has at least one of the following characteristics:
[0011] Feature 1: The hardness of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating is H, and the range of H is 20.0GPa to 25.0GPa; preferably 20.5GPa to 24.7GPa;
[0012] Feature 2: The equivalent elastic modulus of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating is E*, and the range of E* is 185GPa to 245GPa, preferably 189.5GPa to 242.2GPa;
[0013] Feature 3: H / E* of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating is ≥ 0.1; preferably 0.102 to 0.108;
[0014] Feature 4: The friction coefficient of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating in an atmospheric environment of 25°C is 0.090 to 0.100; preferably 0.090 to 0.098;
[0015] Feature 5: The friction coefficient of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating in an atmospheric environment of 400°C is 0.050-0.055;
[0016] Feature 6: The friction coefficient of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating in an atmospheric environment of 500°C is 0.040-0.050;
[0017] Feature 7: The wear rate of high temperature wear-resistant self-lubricating boron-doped diamond-like coating in 25°C atmospheric environment does not exceed 3.50×10 -7 m 3 / N·m;
[0018] Feature 8: The wear rate of high temperature wear-resistant self-lubricating boron-doped diamond-like coating in 400℃ atmospheric environment does not exceed 1.50×10 -6 m 3 / N·m;
[0019] Feature 9: The wear rate of high temperature wear-resistant self-lubricating boron-doped diamond-like coating in 500℃ atmospheric environment does not exceed 5.0×10 -6 m 3 / N·m;
[0020] Feature 10: The high-temperature wear-resistant self-lubricating boron-doped diamond-like coating can form an easy-to-lubricate lamellar amorphous carbon transfer film rich in boron oxide in situ at the wear scar when rubbed at 400°C to 500°C.
[0021] In a second aspect, the present invention provides a method for preparing a high-temperature wear-resistant self-lubricating boron-doped diamond-like coating as described in any of the above embodiments, comprising the following steps: depositing a Cr primer layer, a Cr x B y C z Gradient transition layer and B-DLC functional layer.
[0022] In an optional embodiment, the Cr base layer is prepared by DC magnetron sputtering;
[0023] The preparation conditions of the Cr base layer include: the vacuum degree in the equipment chamber is better than 1.0×10 -3 Pa, 120sccm~150sccm of argon gas is introduced into the equipment, and the gas pressure is maintained at 0.40Pa~0.45Pa; the substrate bias is -200V to -250V, and the bias duty cycle is 50%~60%; the target current is 1.0A~2.0A, and the deposition time is 5min~10min; the target material is a metal chromium target, in which the Cr content accounts for 99.5wt%~99.99wt%.
[0024] In an optional embodiment, Cr is prepared by DC magnetron sputtering. x B y C z Gradient transition layer;
[0025] Cr x B y C z The preparation conditions of the gradient transition layer include: introducing 120sccm to 150sccm of argon gas into the equipment and maintaining the gas pressure at 0.40Pa to 0.45Pa; the substrate bias is -200V to -250V, and the bias duty cycle is 50 to 60%; the target materials are metal chromium target and graphite-boron carbide composite target; the current of the metal chromium target is gradually reduced from 2.0A to 0A, and the current of the graphite-boron carbide composite target is gradually increased from 0A to 2.0A, and the deposition time is 8min to 12min.
[0026] In an optional embodiment, the B-DLC functional layer is prepared by high-power pulsed magnetron sputtering technology assisted by an anode layer ion source;
[0027] The preparation conditions of the B-DLC functional layer include: introducing 80sccm~100sccm argon gas with a gas pressure of 0.25Pa~0.30Pa; the substrate bias is -100V to -150V, and the bias duty cycle is 50%~60%; using a graphite-boron carbide composite target, in which the B content is 5wt%~10wt%; the HiPIMS pulse power is 2.0kW~4.0kW, and the duty cycle is 1.0%~3.0%; the anode layer ion source power is 0.18kW~0.36kW, and the duty cycle is 50%~60%; the deposition time is 4h~6h.
[0028] In an optional embodiment, before preparing the Cr base layer, the substrate is also pre-treated.
[0029] In an optional embodiment, the pretreatment includes grinding and polishing the substrate, then performing ultrasonic cleaning, placing the obtained substrate on a rotating rack in a vacuum chamber, and finally performing plasma glow cleaning using an anode layer ion source.
[0030] In an optional embodiment, the ultrasonic cleaning time is 40 min to 50 min;
[0031] And / or, the plasma glow cleaning comprises: fixing the substrate on a vacuum chamber rotating frame, and waiting for the vacuum degree to be better than 1.0×10 -3 Pa, introduce 150sccm~200sccm argon gas, maintain the gas pressure at 0.60Pa~0.80Pa; at the same time, adjust the substrate bias to -900V to -1000V, and the bias duty cycle is 50%~60%; then turn on the anode layer ion source, the anode layer ion source power is 0.18kW~0.36kW, the duty cycle is 50%~60%, and the plasma glow cleaning time is 10min~15min.
[0032] In a third aspect, the present invention provides an application of a high-temperature wear-resistant, self-lubricating, boron-doped diamond-like coating as described in any of the aforementioned embodiments. For example, the high-temperature wear-resistant, self-lubricating, boron-doped diamond-like coating can be used to prepare cutting tools, molds, high-tech equipment and their key components.
[0033] In an alternative embodiment, the tool comprises a milling cutter or a micro drill bit moving at high speed.
[0034] In an alternative embodiment, the die comprises a stamping die, a punch, or an ejector pin surface.
[0035] In an optional embodiment, the key components include planetary gears, sun gears or internal gear rings.
[0036] The beneficial effects of the present invention include:
[0037] The present invention deposits a Cr base layer, a Cr layer with a specific thickness, structure and element content on the surface of the substrate. x B y C z The gradient transition layer and the B-DLC functional layer can obtain a high-temperature wear-resistant self-lubricating boron-doped diamond-like coating, which has high hardness, high toughness and low friction characteristics. Especially in a high-temperature atmospheric environment of 400-500°C, the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating exhibits excellent self-lubrication and wear resistance, and can significantly improve the lubrication and wear resistance of the diamond-like film under high-temperature atmospheric conditions.
[0038] The preparation method of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating has the advantages of low deposition temperature, high material utilization rate, good coating uniformity, good repeatability and wide practicability. The obtained high-temperature wear-resistant self-lubricating boron-doped diamond-like coating can be widely used in the fields of high-temperature friction and wear protection of cutting tools, molds, high-tech equipment and their key parts, which greatly broadens the application scope of diamond-like coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0040] Figure 1 This is a scanning electron microscope photograph of the cross-sectional morphology of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating prepared in Example 1;
[0041] Figure 2 The friction coefficient curve and average friction coefficient value of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating prepared in Example 1 at room temperature (25°C), 400°C and 500°C high-temperature atmosphere;
[0042] Figure 3 The wear scar morphology and transfer film of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating prepared in Example 1 after friction at room temperature (25°C), 400°C and 500°C high temperature atmosphere. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0044] The high-temperature wear-resistant self-lubricating boron-doped diamond-like coating provided by the present invention and its preparation method and application are specifically described below.
[0045] The present invention provides a high-temperature wear-resistant self-lubricating boron-doped diamond-like coating, which comprises a Cr base layer, a Cr x B y C z Gradient transition layer and B-DLC functional layer.
[0046] The substrate may illustratively but not limitatively include 304 stainless steel, YG6 hard alloy steel, etc.
[0047] The Cr primer layer has a columnar structure, which can be clearly observed.
[0048] The thickness of the Cr base layer is 0.15 μm to 0.25 μm, such as 0.15 μm, 0.18 μm, 0.20 μm, 0.22 μm or 0.25 μm, etc. It can also be other values within the range of 0.15 μm to 0.25 μm or other ranges.
[0049] If the Cr base layer is thin, it is not conducive to the Cr x B y C z The gradient transition layer forms good adhesion with the substrate; if the Cr base layer is thick, it is not conducive to the Cr x B y C z The performance of the gradient transition layer.
[0050] In the Cr base layer, the mass percentage of Cr is 99.50% to 99.99%, such as 99.50%, 99.55%, 99.60%, 99.65%, 99.70%, 99.75%, 99.80%, 99.85%, 99.90%, 99.95 or 99.99%, etc., and can also be other values within the range of 99.50% to 99.99% or other ranges.
[0051] If the mass percentage of Cr in the Cr base layer is less than 99.50%, it is not conducive to the matrix and Cr x B y C zThe combination between the gradient transition layers causes the coating to easily fall off or crack.
[0052] Cr x B y C z The gradient transition layer has a columnar structure, which can be clearly observed.
[0053] The Cr x B y C z The thickness of the gradient transition layer is 0.05 μm to 0.10 μm, such as 0.05 μm, 0.06 μm, 0.07 μm, 0.08 μm, 0.09 μm or 0.10 μm, etc. It can also be other values within the range of 0.05 μm to 0.10 μm or other ranges.
[0054] If Cr x B y C z The thin gradient transition layer is not conducive to the formation of good adhesion between the B-DLC functional layer and the Cr base layer; if the Cr x B y C z The gradient transition layer is relatively thick, which is not conducive to the performance of the B-DLC functional layer.
[0055] The Cr x B y C z In the gradient transition layer, the mass percentage of Cr is greater than 0 and does not exceed 99.99% (such as 0.5%, 1%, 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% or 99.99%). The mass percentage of B is greater than 0 and does not exceed 8% (such as 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7% or 8%), and the remainder is C.
[0056] From the direction close to the Cr base layer to the direction away from the Cr base layer, Cr x B y C z In the gradient transition layer, the mass percentage of Cr gradually decreases from 99.99% to 0, and the mass percentage of B gradually increases from 0 to 8%.
[0057] If Cr x B y C z The mass percentage of B in the gradient transition layer exceeds 8%, which is not conducive to the Cr x B y C z Combination between gradient transition layer and B-DLC functional layer.
[0058] The B-DLC functional layer has a dense featureless structure, where the above-mentioned “dense” may be understood as a porosity of no more than 1%.
[0059] The thickness of the B-DLC functional layer is 1.0 μm to 2.0 μm, such as 1.0 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm or 2.0 μm, etc. It can also be any other value within the range of 1.0 μm to 2.0 μm or other ranges.
[0060] If the thickness of the B-DLC functional layer is too thin, it is not conducive to the performance of the B-DLC functional layer; if the thickness of the B-DLC functional layer is too thick, the preparation cost of the coating is increased.
[0061] In the B-DLC functional layer, the mass percentage of B is 3% to 5% (such as 3%, 3.5%, 4%, 4.5% or 5%), and the remainder is C. That is, the mass percentage of C in the B-DLC functional layer is 95% to 97% (such as 95%, 95.5%, 96%, 96.5% or 97%).
[0062] If the mass percentage of B in the B-DLC functional layer is lower than 3%, it is not conducive to the formation of sufficient boron-rich oxide with lubrication and wear reduction in the film during the friction process; if the mass percentage of B in the B-DLC functional layer is higher than 5%, it is easy to cause a large amount of hard B4C phase to form in the film, thereby reducing its lubricity.
[0063] In some optional embodiments, the hardness of the high temperature wear-resistant self-lubricating boron-doped diamond-like coating is H, and the range of H is 20.0 GPa to 25.0 GPa. In some preferred embodiments, H is 20.5 GPa to 24.7 GPa, such as 20.5 GPa, 20.6 GPa, 21.1 GPa, 21.4 GPa, 21.6 GPa, 21.9 GPa, 22.1 GPa, 22.5 GPa, 22.6 GPa, 22.9 GPa, 23.6 GPa, 24.2 GPa or 24.7 GPa, and may also be other values within the range of 20.5 GPa to 24.7 GPa or other ranges.
[0064] In some optional embodiments, the equivalent elastic modulus of the high temperature wear-resistant self-lubricating boron-doped diamond-like coating is E*, and the range of E* is 185GPa to 245GPa. In some preferred embodiments, E* is 189.5GPa to 242.2GPa, such as 189.5GPa, 192.5GPa, 193.4GPa, 197.2GPa, 201.9GPa, 203.8GPa, 206.7GPa, 210.5GPa, 213.8GPa, 214.3GPa, 217.3GPa, 218.1GPa, 224.1GPa, 226.9GPa, 235.0GPa or 242.2GPa, and can also be other values within the range of 189.5GPa to 242.2GPa or other ranges. The above E*=E / (1-ν 2 ), where E is the elastic modulus and ν is the Poisson's ratio.
[0065] In some optional embodiments, the H / E* of the high temperature wear-resistant self-lubricating boron-doped diamond-like coating is ≥ 0.1. In some preferred embodiments, H / E* is 0.102 to 0.108, such as 0.102, 0.103, 0.104, 0.105, 0.106, 0.107 or 0.108, and may be other values within the range of 0.102 to 0.108 or other ranges.
[0066] In some optional embodiments, the friction coefficient of the high temperature wear-resistant self-lubricating boron-doped diamond-like coating in an atmospheric environment of 25°C is 0.090-0.100. In some preferred embodiments, the friction coefficient of the high temperature wear-resistant self-lubricating boron-doped diamond-like coating in an atmospheric environment of 25°C is 0.090-0.098, such as 0.090, 0.091, 0.092, 0.093, 0.094, 0.096, 0.097 or 0.098, etc., and can also be other values within the range of 0.090-0.098 or other ranges.
[0067] In some optional embodiments, the friction coefficient of the high temperature wear-resistant self-lubricating boron-doped diamond-like coating in an atmospheric environment of 400°C is 0.050-0.055, such as 0.050, 0.051, 0.052, 0.053, 0.054 or 0.055, etc., or may be other values within the range of 0.050-0.055 or other ranges.
[0068] In some optional embodiments, the friction coefficient of the high temperature wear-resistant self-lubricating boron-doped diamond-like coating in an atmospheric environment of 500°C is 0.040-0.050, such as 0.040, 0.042, 0.043, 0.044, 0.046, 0.047, 0.049 or 0.050, etc., or may be other values within the range of 0.040-0.050 or other ranges.
[0069] In some optional embodiments, the wear rate of the high temperature wear-resistant self-lubricating boron-doped diamond-like coating in an atmospheric environment of 25°C is no more than 3.50×10 -7 m 3 / N·m. In some preferred embodiments, the wear rate of the high temperature wear-resistant self-lubricating boron-doped diamond-like coating in an atmospheric environment at 25°C is 1.02×10 -7 m 3 / N·m~3.50×10 -7 m 3 / N·m, such as 1.02×10 -7 m 3 / N·m, 1.88×10 -7 m 3 / N·m, 1.24×10 -7 m 3 / N·m, 2.06×10 -7 m 3 / N·m, 2.16×10 - 7 m 3 / N·m, 2.18×10 -7 m 3 / N·m, 2.24×10 -7 m 3 / N·m, 2.33×10 -7 m 3 / N·m, 2.34×10 -7 m 3 / N·m, 2.35×10 -7 m 3 / N·m, 2.45×10 -7 m 3 / N·m, 2.67×10 -7 m 3 / N·m,3.22×10 -7 m 3 / N·m、3.41×10 - 7 m 3 / N·m or 3.50×10 -7 m 3 / N·m, etc., or 1.02×10 -7m 3 / N·m~3.50×10 -7 m 3 / N·m or other ranges.
[0070] In some optional embodiments, the wear rate of the high temperature wear-resistant self-lubricating boron-doped diamond-like coating in an atmospheric environment of 400°C is no more than 1.50×10 -6 m 3 / N·m. In some preferred embodiments, the wear rate of the high temperature wear-resistant self-lubricating boron-doped diamond-like coating in an atmospheric environment at 400°C can be 1.04×10 -6 m 3 / N·m~1.50×10 -6 m 3 / N·m, such as 1.04×10 -6 m 3 / N·m, 1.08×10 -6 m 3 / N·m, 1.16×10 -6 m 3 / N·m, 1.19×10 -6 m 3 / N·m, 1.21×10 -6 m 3 / N·m, 1.22×10 -6 m 3 / N·m, 1.23×10 -6 m 3 / N·m, 1.26×10 -6 m 3 / N·m, 1.29×10 - 6 m 3 / N·m, 1.35×10 -6 m 3 / N·m, 1.37×10 -6 m 3 / N·m, 1.42×10 -6 m 3 / N·m, 1.47×10 -6 m 3 / N·m or 1.50×10 -6 m 3 / N·m, etc., or 1.04×10 -6 m 3 / N·m~1.50×10 -6 m 3 / N·m or other ranges.
[0071] In some optional embodiments, the wear rate of the high temperature wear-resistant self-lubricating boron-doped diamond-like coating in an atmospheric environment of 500°C is no more than 5.0×10 -6 m 3 In some preferred embodiments, the wear rate of the high temperature wear-resistant self-lubricating boron-doped diamond-like coating in an atmospheric environment of 500°C can be 2.05×10 -6 m 3 / N·m~4.97×10 -6 m 3 / N·m, such as 2.05×10 -6 m 3 / N·m, 2.15×10 -6 m 3 / N·m, 2.33×10 -6 m 3 / N·m, 2.51×10 -6 m 3 / N·m, 2.61×10 -6 m 3 / N·m, 2.61×10 -6 m 3 / N·m, 2.74×10 -6 m 3 / N·m, 2.85×10 -6 m 3 / N·m, 2.94×10 -6 m 3 / N·m、3.29×10 -6 m 3 / N·m、3.35×10 -6 m 3 / N·m、3.45×10 -6 m 3 / N·m,3.51×10 -6 m 3 / N·m or 4.97×10 -6 m 3 / N·m, etc., or 2.05×10 -6 m 3 / N·m~4.97×10 -6 m 3 / N·m or other ranges.
[0072] In the high-temperature wear-resistant self-lubricating boron-doped diamond-like carbon coating of the present invention, the doping of B can not only stabilize the amorphous structure of the DLC coating and effectively inhibit the graphitization tendency, but also optimize the lubrication mechanism by promoting the formation of the transfer film, and significantly improve the self-lubricating performance of the DLC coating at higher temperatures. In addition, the doping of B can also generate a hard boron carbide phase inside the coating, further enhancing the hardness and wear resistance of the coating.
[0073] It should be emphasized that the inventors creatively discovered that doping with B can have the following advantages over doping with Si: B incorporation can not only stabilize the amorphous structure of the DLC coating and reduce the tendency to graphitization, but also have a positive effect on its lubrication mechanism by promoting the formation of a transfer film, thereby improving its self-lubricating performance at high temperatures. In addition, B doping will also form a hard boron carbide phase inside the coating, further enhancing the hardness and wear resistance of the coating.
[0074] In the present invention, a Cr base layer, a Cr x B y C z The gradient transition layer and the B-DLC functional layer can obtain a high-temperature wear-resistant self-lubricating boron-doped diamond-like coating, which has high hardness, high toughness and low friction characteristics. Especially in a high-temperature atmospheric environment of 400-500°C, the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating can form an easy-to-lubricate lamellar amorphous carbon transfer film rich in boron oxide in situ at the wear scar, which can effectively reduce the friction coefficient, show excellent self-lubricating and wear-resistant properties, and have excellent lubrication and friction reduction effects at high temperatures.
[0075] Accordingly, the present invention also provides a method for preparing the above-mentioned high-temperature wear-resistant self-lubricating boron-doped diamond-like coating, comprising the following steps: depositing a Cr primer layer, a Cr x B y C z Gradient transition layer and B-DLC functional layer.
[0076] In some optional embodiments, the Cr base layer is prepared by DC magnetron sputtering.
[0077] The preparation conditions of the Cr bottom layer may include: the vacuum degree in the equipment chamber is better than 1.0×10 -3Pa, 120 sccm to 150 sccm (such as 120 sccm, 125 sccm, 130 sccm, 135 sccm, 140 sccm, 145 sccm or 150 sccm, etc.) of argon is introduced into the equipment to maintain the gas pressure at 0.40 Pa to 0.45 Pa (such as 0.40 Pa, 0.41 Pa, 0.42 Pa, 0.43 Pa, 0.44 Pa or 0.45 Pa, etc.); the substrate bias voltage is -20 0V to -250V (such as -200V, -210V, -220V, -230V, -240V or -250V, etc.), the bias duty cycle is 50% to 60% (such as 50%, 55% or 60%, etc.); the target current is 1.0A to 2.0A (such as 1.0A, 1.5A or 2.0A, etc.), and the deposition time is 5min to 10min (such as 5min, 6min, 7min, 8min, 9min or 10min, etc.).
[0078] The target material used in the above-mentioned Cr base layer preparation process is a metal chromium target, wherein the mass percentage of Cr is 99.50% to 99.99%.
[0079] In some optional embodiments, Cr is prepared by DC magnetron sputtering. x B y C z Gradient transition layer.
[0080] Cr x B y C z The preparation conditions of the gradient transition layer include: introducing 120sccm~150sccm (such as 120sccm, 125sccm, 130sccm, 135sccm, 140sccm, 145sccm or 150sccm, etc.) of argon gas into the equipment, maintaining the gas pressure at 0.40Pa~0.45Pa (such as 0.40Pa, 0.41Pa, 0.42Pa, 0.43Pa, 0.44Pa or 0.45Pa, etc.); the substrate bias is -200V to -250V (such as -200V, -210V, -220V, -230V, -240V or -250V, etc.), and the bias duty cycle is 50%~60% (such as 50%, 55% or 60%, etc.). The target materials include a metal chromium target and a graphite-boron carbide composite target (C-B4C composite target); the current of the metal chromium target is gradually reduced from 2.0A to 0A, and the current of the graphite-boron carbide composite target is gradually increased from 0A to 2.0A, and the deposition time is 8min to 12min (such as 8min, 9min, 10min, 11min or 12min, etc.).
[0081] It should be noted that Cr x B y C zThe metal chromium target and graphite-boron carbide composite target used in the preparation of the gradient transition layer, wherein the metal chromium target is the same as the target material used in the preparation of the Cr base layer, and the graphite-boron carbide composite target is the same as the target material used in the preparation of the B-DLC functional layer.
[0082] In some optional embodiments, the B-DLC functional layer is prepared by high-power pulsed magnetron sputtering technology assisted by an anode ion source.
[0083] The preparation conditions of the B-DLC functional layer may include: an argon gas flow rate of 80 sccm to 100 sccm (such as 80 sccm, 85 sccm, 90 sccm, 95 sccm or 100 sccm, etc.), a gas pressure of 0.25 Pa to 0.30 Pa (such as 0.25 Pa, 0.26 Pa, 0.27 Pa, 0.28 Pa, 0.29 Pa or 0.30 Pa, etc.); a substrate bias of -100 V to -150 V (such as -100 V, -110 V, -120 V, -130 V, -140 V or -150 V, etc.), and a bias duty cycle of 50% to 60% (such as 50%, 55% or 60%, etc.). A graphite-boron carbide composite target is used, wherein the B content is 5wt% to 10wt% (such as 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%), the HiPIMS pulse power is 2.0kW to 4.0kW (such as 2.0kW, 2.5kW, 3.0kW, 3.5kW or 4.0kW, etc.), and the duty cycle is 1.0% to 3.0% (such as 1.0%, 1.5%, 2.0%, 2.5kW, etc.). .5% or 3.0%, etc.); the anode layer ion source power is 0.18kW~0.36kW (such as 0.18kW, 0.21kW, 0.24kW, 0.27kW, 0.30kW, 0.33kW or 0.36kW, etc.), the duty cycle is 50%~60% (such as 50%, 55% or 60%, etc.); the deposition time is 4h~6h (such as 4.0h, 4.5h, 5.0h, 5.5h or 6.0h, etc.).
[0084] The above-mentioned high-power pulsed magnetron sputtering deposition technology assisted by the anode layer ion source has an extremely high ionization rate and high bombardment energy, and is easier to prepare a composite lubricating coating with special properties.
[0085] For reference, the equipment used in the high-power pulsed magnetron sputtering deposition technology assisted by the anode layer ion source adopted in this application mainly includes a vacuum chamber, a turret system, a DC power supply, a high-power pulsed power supply, an anode layer ion source, an air intake unit and a molecular pump, wherein the DC power supply, the anode layer ion source and the high-power pulsed power supply are evenly distributed on the inner wall of the vacuum chamber, and a turret capable of revolution and rotation is provided in the vacuum chamber. The DC power supply is installed on the metal chromium target, the high-power pulsed power supply is installed on the C-B4C composite target, and the substrate is installed on the turret. Regarding the equipment and deposition principle used for the high-power pulsed magnetron sputtering and DC magnetron sputtering deposition assisted by the anode layer ion source, reference can be made to the relevant contents of high-power pulsed magnetron sputtering and DC magnetron sputtering, and no excessive restrictions are made here.
[0086] In some embodiments, before preparing the Cr base layer, the substrate is also pre-treated.
[0087] The pretreatment includes grinding and polishing the substrate, then ultrasonic cleaning, and then placing the obtained substrate on a rotating rack in a vacuum chamber and performing plasma glow cleaning using an anode layer ion source.
[0088] Among them, ultrasonic cleaning refers to ultrasonic cleaning in alkaline detergent and deionized water, and the ultrasonic cleaning time can be 40min to 50min, such as 40min, 42min, 45min, 48min or 50min, etc., or other values within the range of 40min to 50min.
[0089] Plasma glow cleaning may include placing the substrate in a vacuum chamber and evacuating the chamber to a vacuum better than 1.0×10 -3 Pa, then introduce 150sccm~200sccm (such as 150sccm, 160sccm, 170sccm, 180sccm, 190sccm or 200sccm, etc.) of argon gas, adjust the gas pressure to 0.60Pa~0.80Pa (such as 0.60Pa, 0.65Pa, 0.70Pa, 0.75Pa or 0.80Pa, etc.); at the same time, adjust the substrate bias to -900V to -1000V (such as -900V, -950V or -1000V, etc.), and the bias duty cycle is 50%~60% (such as 50%, 55% or 60%, etc.); then turn on the anode layer ion source, the anode layer ion source power is 0.18kW~0.36kW (such as 0.18kW, 0.21kW, 0.24kW, 0.27kW, 0.30kW, 0.33kW or 0.36kW, etc.), the duty cycle is 50%~60% (such as 50%, 55% or 60%, etc.), and the plasma glow cleaning time is 10min~15min (such as 10min, 11min, 12min, 13min, 14min or 15min, etc.).
[0090] In the present invention, the high temperature wear-resistant self-lubricating boron-doped diamond-like coating, wherein the boron doping significantly changes the microstructure and performance of the DLC coating, and improves its hardness and wear resistance. In the process of realizing this design, DC magnetron sputtering is used to deposit the Cr base layer and Cr x B y C z Gradient transition layer, and high-power pulsed magnetron sputtering equipment assisted by anode layer ion source to deposit functional layer. High-power pulsed magnetron sputtering technology can generate high-energy plasma, and significantly increase the ionization rate of sputtering gas through ion source assistance, thereby enhancing the bombardment energy during the deposition process. This series of optimizations not only improves the quality of the film, but also brings significant improvements in key properties such as toughness, wear resistance, and bonding strength. Compared with traditional magnetron sputtering equipment, high-power pulsed magnetron sputtering technology assisted by anode layer ion source is easier to prepare composite lubricating coatings with special properties.
[0091] Through the specific preparation method and preparation conditions provided by the present invention, a high-temperature wear-resistant self-lubricating boron-doped diamond-like coating having high hardness, high toughness and low friction performance is effectively prepared.
[0092] In addition, the present invention also provides an application of the above-mentioned high-temperature wear-resistant self-lubricating boron-doped diamond-like coating. For example, the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating can be used to prepare cutting tools, molds, high-tech equipment and its key components.
[0093] The tool may exemplarily include a high-speed milling cutter or a micro drill bit, etc. The mold may exemplarily include a stamping mold, a punch or an ejector surface, etc. The key components may exemplarily include a planetary gear, a sun gear or an internal gear ring, etc.
[0094] The high-toughness, wear-resistant, high-temperature wear-resistant, self-lubricating boron-doped diamond-like coating provided by the present invention and its preparation method and application are specifically described below.
[0095] Example 1
[0096] This embodiment provides a high-toughness, wear-resistant, high-temperature wear-resistant, self-lubricating boron-doped diamond-like coating, which is prepared by the following method:
[0097] S1: substrate pretreatment.
[0098] The 304 stainless steel substrate was ultrasonically cleaned for 45 minutes with alkaline cleaning agent and deionized water respectively, and then the dried substrate was installed on a rotating rack. Then the vacuum operation was carried out, and the background vacuum was better than 1.0×10-3Pa; 180sccm argon gas was introduced and the gas pressure was adjusted to 0.72Pa; the substrate bias was adjusted to -1000V and the duty cycle was 60%; the anode layer ion source was turned on, the power was set to 0.25kW, and the duty cycle was 60%, and the substrate was plasma glow cleaned for 15 minutes.
[0099] S2: Prepare a Cr base layer on the surface of the substrate.
[0100] After plasma glow cleaning, 120sccm of argon gas was introduced into the equipment to maintain the gas pressure at 0.40Pa; the substrate bias voltage was -250V, the bias duty cycle was 60%; the target current was 2.0A, and the deposition time was 5min to form a Cr base layer. The target material was a metal chromium target, in which the Cr content accounted for 99.80wt%.
[0101] S3: Preparation of Cr on the surface of Cr base layer x B y C z Gradient transition layer.
[0102] After the Cr base deposition is completed, 120sccm of argon gas is continued to be introduced to maintain the gas pressure at 0.40Pa; the substrate bias is -250V, and the bias duty cycle is 60%; the target materials are metal chromium target and graphite-boron carbide (C-B4C) composite target; the current of the metal chromium target is gradually reduced from 2.0A to 0A, and the current of the C-B4C embedded composite target is gradually increased from 0A to 2.0A, and the deposition time is 10min to form Cr. x B y C z Gradient transition layer.
[0103] S4: In Cr x B y C z A B-DLC functional layer is prepared on the surface of the gradient transition layer.
[0104] Cr x B y C zAfter the gradient transition layer is deposited, 90sccm argon gas is introduced with a pressure of 0.28Pa; the substrate bias is -125V, and the bias duty cycle is 60%; a graphite-boron carbide (C-B4C) composite target is used, and the B content accounts for 8wt%, the HiPIMS pulse power is 3.0kW, and the duty cycle is 1.0%; the anode layer ion source assists the ionization of the sputtering gas, and the corresponding anode layer ion source power is 0.25kW, and the duty cycle is 60%; the deposition time is 4h, and the B-DLC functional layer is formed. The rotation speed of the rotating frame is stable at 2rpm during the entire deposition process, and it is naturally cooled after the preparation is completed.
[0105] Figure 1 This is a scanning electron microscope photo of the cross section of the coating sample prepared in this embodiment, from bottom to top, 304 stainless steel substrate, Cr base layer, Cr x B y C z Gradient transition layer and B-DLC functional layer. From this figure, it can be seen that the B-DLC functional layer can x B y C z The gradient transition layer grows well, Cr x B y C z The gradient transition layer can grow well on the Cr base layer. x B y C z The gradient transition layer presents an obvious columnar structure, and the B-DLC functional layer presents a dense featureless structure.
[0106] After testing, the total thickness of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating obtained in this embodiment is 1.04 μm, of which the thickness of the Cr base layer is 0.15 μm and the thickness of the Cr base layer is 0.15 μm. x B y C z The thickness of the gradient transition layer is 0.05 μm, and the thickness of the B-DLC functional layer is 0.84 μm. The mass percentage of Cr in the Cr base layer is 99.80%. x B y C z In the gradient transition layer, the mass percentage of Cr is 0-99.99%, the mass percentage of B is 0-8%, and the remainder is C (in the direction from close to the Cr base layer to far away from the Cr base layer, Cr x B y C z In the gradient transition layer, the mass percentage of Cr gradually decreases, and the mass percentage of B gradually increases). In the B-DLC functional layer, the mass percentage of B is 3.36%, and the mass percentage of C is 96.64%.
[0107] Example 2
[0108] The difference between this embodiment and embodiment 1 is that the substrate of this embodiment is YG6 cemented carbide.
[0109] The total thickness of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating obtained in this embodiment is 1.04 μm, of which the thickness of the Cr base layer is 0.15 μm and the thickness of the Cr base layer is 0.15 μm. x B y C z The thickness of the gradient transition layer is 0.05 μm, and the thickness of the B-DLC functional layer is 0.84 μm. The mass percentage of Cr in the Cr base layer is 99.80%. x B y C z In the gradient transition layer, the mass percentage of Cr is 0-99.99%, the mass percentage of B is 0-8%, and the balance is C. In the B-DLC functional layer, the mass percentage of B is 3.36%, and the mass percentage of C is 96.64%.
[0110] Example 3
[0111] The difference between this embodiment and embodiment 1 is that in this embodiment, the substrate bias voltage is -100V when depositing the B-DLC functional layer.
[0112] The total thickness of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating obtained in this embodiment is 1.18 μm, of which the thickness of the Cr base layer is 0.15 μm and the thickness of the Cr base layer is 0.15 μm. x B y C z The thickness of the gradient transition layer is 0.05 μm, the thickness of the B-DLC functional layer is 0.98 μm, and the mass percentage of B in the B-DLC functional layer is 3.04% and the mass percentage of C is 96.96%.
[0113] The rest is the same as in Example 1.
[0114] Example 4
[0115] The difference between this embodiment and embodiment 1 is that in this embodiment, the substrate bias voltage is -150V when depositing the B-DLC functional layer.
[0116] The total thickness of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating obtained in this embodiment is 1.10 μm, of which the thickness of the Cr base layer is 0.15 μm and the thickness of the Cr base layer is 0.15 μm. x B y C z The thickness of the gradient transition layer is 0.05 μm, the thickness of the B-DLC functional layer is 0.90 μm, and the mass percentage of B in the B-DLC functional layer is 3.14% and the mass percentage of C is 96.86%.
[0117] The rest is the same as in Example 1.
[0118] Example 5
[0119] The difference between this embodiment and embodiment 1 is that in this embodiment, 80 sccm of argon gas is introduced during the deposition of the B-DLC functional layer, and the gas pressure is adjusted to 0.25 Pa.
[0120] The total thickness of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating obtained in this embodiment is 1.02 μm, of which the thickness of the Cr base layer is 0.15 μm and the thickness of the Cr base layer is 0.15 μm. x B y C z The thickness of the gradient transition layer is 0.05 μm, the thickness of the B-DLC functional layer is 0.82 μm, and the mass percentage of B in the B-DLC functional layer is 3.08%, and the mass percentage of C is 96.92%.
[0121] The rest is the same as in Example 1.
[0122] Example 6
[0123] The difference between this embodiment and embodiment 1 is that in this embodiment, 100 sccm of argon gas is introduced when depositing the B-DLC functional layer, and the gas pressure is adjusted to 0.30 Pa.
[0124] The total thickness of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating obtained in this embodiment is 1.17 μm, of which the thickness of the Cr base layer is 0.15 μm and the thickness of the Cr base layer is 0.15 μm. x B y C z The thickness of the gradient transition layer is 0.05 μm, the thickness of the B-DLC functional layer is 0.97 μm, and the mass percentage of B in the B-DLC functional layer is 3.91% and the mass percentage of C is 96.09%.
[0125] The rest is the same as in Example 1.
[0126] Example 7
[0127] The difference between this embodiment and embodiment 1 is that the deposition time of the B-DLC functional layer in this embodiment is 6 hours.
[0128] The total thickness of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating obtained in this embodiment is 1.43 μm, of which the thickness of the Cr base layer is 0.15 μm and the thickness of the Cr base layer is 0.15 μm. x B y C z The thickness of the gradient transition layer is 0.05 μm, the thickness of the B-DLC functional layer is 1.23 μm, and the mass percentage of B in the B-DLC functional layer is 3.38%, and the mass percentage of C is 96.62%.
[0129] The rest is the same as in Example 1.
[0130] Example 8
[0131] The difference between this embodiment and embodiment 1 is that the HiPIMS pulse power during the deposition of the B-DLC functional layer in this embodiment is 4.0 kW.
[0132] The total thickness of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating obtained in this embodiment is 1.46 μm, of which the thickness of the Cr base layer is 0.15 μm and the thickness of the Cr base layer is 0.15 μm. x B y C z The thickness of the gradient transition layer is 0.05 μm, the thickness of the B-DLC functional layer is 1.26 μm, and the mass percentage of B in the B-DLC functional layer is 3.71% and the mass percentage of C is 96.29%.
[0133] The rest is the same as in Example 1.
[0134] Example 9
[0135] This embodiment is similar to Embodiment 1 except that the power of the anode layer ion source in this embodiment is 0.18 kW.
[0136] The total thickness of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating obtained in this embodiment is 1.47 μm, of which the thickness of the Cr base layer is 0.15 μm and the thickness of the Cr base layer is 0.15 μm. x B y C z The thickness of the gradient transition layer is 0.05 μm, the thickness of the B-DLC functional layer is 1.27 μm, and the mass percentage of B in the B-DLC functional layer is 3.25%, and the mass percentage of C is 96.75%.
[0137] The rest is the same as in Example 1.
[0138] Example 10
[0139] The difference between this embodiment and embodiment 1 is that the power of the anode layer ion source in this embodiment is 0.36 kW.
[0140] The total thickness of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating obtained in this embodiment is 1.02 μm, of which the thickness of the Cr base layer is 0.15 μm and the thickness of the Cr base layer is 0.15 μm. x B y C z The thickness of the gradient transition layer is 0.05 μm, the thickness of the B-DLC functional layer is 0.82 μm, and the mass percentage of B in the B-DLC functional layer is 3.65% and the mass percentage of C is 96.35%.
[0141] The rest is the same as in Example 1.
[0142] Embodiment 11
[0143] The difference between this embodiment and embodiment 1 is that: in this embodiment, 80 sccm argon gas is introduced when depositing the B-DLC functional layer, and the gas pressure is 0.25 Pa; the substrate bias is -150 V, and the bias duty cycle is 60%; a graphite-boron carbide (C-B4C) composite target is used, the B content accounts for 8wt%, the HiPIMS pulse power is 2.0kW, and the duty cycle is 1.0%; the anode layer ion source is used to assist the ionization of the sputtering gas, and the corresponding anode layer ion source power is 0.36kW; the deposition time is 4h.
[0144] The total thickness of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating obtained in this embodiment is 1.00 μm, of which the thickness of the Cr base layer is 0.15 μm and the thickness of the Cr base layer is 0.15 μm. x B y C z The thickness of the gradient transition layer is 0.05 μm, the thickness of the B-DLC functional layer is 0.80 μm, and the mass percentage of B in the B-DLC functional layer is 3.36% and the mass percentage of C is 96.64%.
[0145] The rest is the same as in Example 1.
[0146] Example 12
[0147] The difference between this embodiment and embodiment 1 is that: in this embodiment, 100 sccm argon gas is introduced when depositing the B-DLC functional layer, and the gas pressure is 0.30 Pa; the substrate bias is -100 V, and the bias duty cycle is 60%; a graphite-boron carbide (C-B4C) composite target is used, and the B content accounts for 8wt%; the HiPIMS pulse power is 4.0kW, and the duty cycle is 1.0%; the anode layer ion source power is 0.18kW, and the duty cycle is 60%; and the deposition time is 6h.
[0148] The total thickness of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating obtained in this embodiment is 2.20 μm, of which the thickness of the Cr base layer is 0.15 μm and the thickness of the Cr base layer is 0.15 μm. x B y C z The thickness of the gradient transition layer is 0.05 μm, the thickness of the B-DLC functional layer is 2.00 μm, and the mass percentage of B in the B-DLC functional layer is 3.36% and the mass percentage of C is 96.64%.
[0149] The rest is the same as in Example 1.
[0150] Example 13
[0151] This embodiment provides a high-temperature wear-resistant self-lubricating boron-doped diamond-like coating, which is prepared by the following method:
[0152] S1: substrate pretreatment.
[0153] The 304 stainless steel substrate was ultrasonically cleaned for 45 minutes using alkaline cleaning agent and deionized water respectively, and then the dried substrate was installed on a rotating rack. Then the vacuum operation was performed, and the background vacuum degree was better than 1.0×10 -3 Pa; introduce 200 sccm argon gas and adjust the gas pressure to 0.80 Pa; adjust the substrate bias to -1000 V and the duty cycle to 60%; turn on the anode layer ion source, set the power to 0.36 kW and the duty cycle to 60%, and perform plasma glow cleaning on the substrate for 15 minutes.
[0154] S2: Prepare a Cr base layer on the surface of the substrate.
[0155] After plasma glow cleaning, 150 sccm of argon gas was introduced into the equipment to maintain the gas pressure at 0.45 Pa; the substrate bias was -200 V, and the bias duty cycle was 50%; the target current was 1.0 A, and the deposition time was 10 min to form a Cr base layer.
[0156] S3: Preparation of Cr on the surface of Cr base layer x B y C z Gradient transition layer.
[0157] After the Cr base deposition is completed, 150sccm of argon gas is continued to be introduced to maintain the gas pressure at 0.45Pa; the substrate bias is -200V, and the bias duty cycle is 50%; the target materials are metal chromium target and graphite-boron carbide (C-B4C) composite target; the current of the metal chromium target is gradually reduced from 2.0A to 0A, and the current of the C-B4C embedded composite target is gradually increased from 0A to 2.0A, and the deposition time is 10min to form Cr. x B y C z Gradient transition layer.
[0158] S4: In Cr x B y C z A B-DLC functional layer is prepared on the surface of the gradient transition layer.
[0159] Cr x B y C zAfter the gradient transition layer is deposited, 100sccm argon gas is introduced with a pressure of 0.30Pa; the substrate bias is -150V, and the bias duty cycle is 50%; a graphite-boron carbide (C-B4C) composite target is used, and the B content accounts for 5wt%, the HiPIMS pulse power is 3.0kW, and the duty cycle is 3.0%; the anode layer ion source assists the ionization of the sputtering gas, and the corresponding anode layer ion source power is 0.36kW, and the duty cycle is 50%; the deposition time is 6h, and the B-DLC functional layer is formed. The rotation speed of the rotating frame is stable at 2rpm during the entire deposition process, and it is naturally cooled after the preparation is completed.
[0160] After testing, the total thickness of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating obtained in this embodiment is 2.16 μm, of which the thickness of the Cr base layer is 0.25 μm and the thickness of the Cr base layer is 0.25 μm. x B y C z The thickness of the gradient transition layer is 0.05 μm, the thickness of the B-DLC functional layer is 1.86 μm, and in the B-DLC functional layer, the mass percentage of B is 3.00%, and the mass percentage of C is 97.00%.
[0161] Embodiment 14
[0162] This embodiment provides a high-toughness, wear-resistant, high-temperature wear-resistant, self-lubricating boron-doped diamond-like coating, which is prepared by the following method:
[0163] S1: substrate pretreatment.
[0164] The 5 mm thick 304 stainless steel substrate was ultrasonically cleaned for 45 min using alkaline cleaning agent and deionized water respectively, and then the dried substrate was mounted on a rotating rack. Then, the vacuum operation was performed, and the background vacuum degree was better than 1.0×10 -3 Pa; introduce 200 sccm argon gas and adjust the gas pressure to 0.80 Pa; adjust the substrate bias to -1000 V and the duty cycle to 60%; turn on the anode layer ion source, set the power to 0.36 kW and the duty cycle to 60%, and perform plasma glow cleaning on the substrate for 15 minutes.
[0165] S2: Prepare a Cr base layer on the surface of the substrate.
[0166] After plasma glow cleaning, 150 sccm of argon gas was introduced into the equipment to maintain the gas pressure at 0.45 Pa; the substrate bias was -200 V, and the bias duty cycle was 50%; the target current was 1.0 A, and the deposition time was 10 min to form a Cr base layer.
[0167] S3: Preparation of Cr on the surface of Cr base layer x B y C z Gradient transition layer.
[0168] After the Cr base deposition is completed, 150sccm of argon gas is continued to be introduced to maintain the gas pressure at 0.45Pa; the substrate bias is -200V, and the bias duty cycle is 50%; the target materials are metal chromium target and graphite-boron carbide (C-B4C) composite target; the current of the metal chromium target is gradually reduced from 2.0A to 0A, and the current of the C-B4C embedded composite target is gradually increased from 0A to 2.0A, and the deposition time is 10min to form Cr. x B y C z Gradient transition layer.
[0169] S4: In Cr x B y C z A B-DLC functional layer is prepared on the surface of the gradient transition layer.
[0170] Cr x B y C z After the gradient transition layer is deposited, 100sccm argon gas is introduced with a pressure of 0.30Pa; the substrate bias is -150V, and the bias duty cycle is 50%; a graphite-boron carbide (C-B4C) composite target is used, the B content accounts for 10wt%, the HiPIMS pulse power is 3.0kW, and the duty cycle is 1.0%; the anode layer ion source assists the ionization of the sputtering gas, and the corresponding anode layer ion source power is 0.36kW, and the duty cycle is 50%; the deposition time is 6h, and the B-DLC functional layer is formed. The rotation speed of the rotating frame is stable at 2rpm during the entire deposition process, and it is naturally cooled after the preparation is completed.
[0171] After testing, the total thickness of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating obtained in this embodiment is 2.24 μm, of which the thickness of the Cr base layer is 0.25 μm and the thickness of the Cr base layer is 0.25 μm. x B y C z The thickness of the gradient transition layer is 0.05 μm, the thickness of the B-DLC functional layer is 1.94 μm, and the mass percentage of B in the B-DLC functional layer is 7.85% and the mass percentage of C is 92.15%.
[0172] Comparative Example 1
[0173] The difference between this comparative example and Example 1 is that this comparative example deposits the B-DLC functional layer by DC magnetron sputtering, and the conditions of DC magnetron sputtering include: introducing 90sccm argon gas, maintaining the gas pressure at 0.28Pa; substrate bias voltage is -125V, and the bias duty cycle is 60%; turning on the DC power supply for deposition, using a graphite-boron carbide (C-B4C) composite target, and the B content accounts for 8wt%; DC target current is 3.0A, and DC target voltage is 1000V; the anode layer ion source assists the ionization of the sputtering gas, and the corresponding anode layer ion source power is 0.25kW, and the duty cycle is 60%; the deposition time is 4h, and the B-DLC functional layer is formed. The rotation speed of the rotating rack is stable at 2rpm during the entire deposition process, and it is naturally cooled after the preparation is completed.
[0174] The total thickness of the high-toughness, wear-resistant, high-temperature wear-resistant, self-lubricating boron-doped diamond-like coating obtained in this comparative example is 1.16 μm, wherein the thickness of the Cr base layer is 0.15 μm, and the thickness of the Cr base layer is 0.15 μm. x B y C z The thickness of the gradient transition layer is 0.05 μm, the thickness of the B-DLC functional layer is 0.96 μm, and the mass percentage of B in the B-DLC functional layer is 2.95%, and the mass percentage of C is 97.05%.
[0175] Comparative Example 2
[0176] The difference between this comparative example and Example 1 is that the Ar flow rate during the preparation of the B-DLC functional layer is 120 sccm and the gas pressure is maintained at 0.35 Pa.
[0177] The total thickness of the high-toughness, wear-resistant, high-temperature wear-resistant, self-lubricating boron-doped diamond-like coating obtained in this comparative example is 1.59 μm, wherein the thickness of the Cr base layer is 0.15 μm, and the thickness of the Cr base layer is 0.15 μm. x B y C z The thickness of the gradient transition layer is 0.05 μm, the thickness of the B-DLC functional layer is 1.39 μm, and the mass percentage of B in the B-DLC functional layer is 2.64% and the mass percentage of C is 97.36%.
[0178] Comparative Example 3
[0179] The difference between this comparative example and Example 1 is that the substrate bias voltage during the preparation of the B-DLC functional layer is 0V.
[0180] The total thickness of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating obtained in this comparative example is 1.72 μm, of which the thickness of the Cr primer layer is 0.15 μm and the thickness of the Cr primer layer is 0.15 μm. x B y C zThe thickness of the gradient transition layer is 0.05 μm, the thickness of the B-DLC functional layer is 1.52 μm, and the mass percentage of B in the B-DLC functional layer is 2.50%, and the mass percentage of C is 97.50%.
[0181] Comparative Example 4
[0182] The difference between this comparative example and Example 1 is that the ion source power of the anode layer during the preparation of the B-DLC functional layer is 0 W.
[0183] The total thickness of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating obtained in this comparative example is 1.43 μm, of which the thickness of the Cr primer layer is 0.15 μm and the thickness of the Cr primer layer is 0.15 μm. x B y C z The thickness of the gradient transition layer is 0.05 μm, the thickness of the B-DLC functional layer is 1.23 μm, and the mass percentage of B in the B-DLC functional layer is 2.42% and the mass percentage of C is 97.58%.
[0184] Comparative Example 5
[0185] The difference between this comparative example and Example 1 is that the power of the anode layer ion source during the preparation of the B-DLC functional layer is 0.5 kW.
[0186] The total thickness of the high-toughness, wear-resistant, high-temperature wear-resistant, self-lubricating boron-doped diamond-like coating of this comparative example is 0.88 μm, of which the thickness of the Cr base layer is 0.15 μm, and the thickness of the Cr base layer is 0.15 μm. x B y C z The thickness of the gradient transition layer is 0.05 μm, the thickness of the B-DLC functional layer is 0.68 μm, and the mass percentage of B in the B-DLC functional layer is 3.92% and the mass percentage of C is 96.08%.
[0187] Comparative Example 6
[0188] The difference between this comparative example and Example 1 is that the Cr base layer is not deposited in this comparative example.
[0189] The total thickness of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating obtained in this comparative example is 0.89 μm, wherein the thickness of the Cr primer layer is 0 μm, and the thickness of the Cr primer layer is 0 μm. x B y C z The thickness of the gradient transition layer is 0.05 μm, the thickness of the B-DLC functional layer is 0.84 μm, and the mass percentage of B in the B-DLC functional layer is 3.36% and the mass percentage of C is 96.64%.
[0190] Comparative Example 7
[0191] The difference between this comparative example and Example 1 is that an undoped DLC coating is prepared in this comparative example.
[0192] The total thickness of the high-toughness, wear-resistant, high-temperature wear-resistant, self-lubricating boron-doped diamond-like coating obtained in this comparative example is 1.04 μm, wherein the thickness of the Cr base layer is 0.15 μm, and the thickness of the Cr base layer is 0.15 μm. x B y C z The thickness of the gradient transition layer is 0.05 μm, and the thickness of the DLC functional layer is 0.84 μm. In the B-DLC functional layer, the mass percentage of B is 0%, and the mass percentage of C is 100%.
[0193] Comparative Example 8
[0194] The difference between this comparative example and Example 1 is that the silicon-doped diamond-like carbon coating in this comparative example is prepared by the same process.
[0195] The total thickness of the high-toughness, wear-resistant, high-temperature wear-resistant, self-lubricating boron-doped diamond-like coating obtained in this comparative example is 1.04 μm, wherein the thickness of the Cr base layer is 0.15 μm, and the thickness of the Cr base layer is 0.15 μm. x Si y C z The thickness of the gradient transition layer is 0.05 μm, the thickness of the Si-DLC functional layer is 0.84 μm, and the mass percentage of Si in the Si-DLC functional layer is 3.36%, and the mass percentage of C is 96.64%.
[0196] Comparative Example 9
[0197] The difference between this comparative example and Example 1 is that the preparation parameter range of the Cr base layer is adjusted so that the thickness of the Cr base layer is 0.10 μm.
[0198] Comparative Example 10
[0199] The difference between this comparative example and Example 1 is that the preparation parameter range of the Cr base layer is adjusted so that the thickness of the Cr base layer is 0.40 μm.
[0200] Comparative Example 11
[0201] The difference between this comparative example and Example 1 is that the preparation parameter range of the B-DLC functional layer is adjusted so that the thickness of the B-DLC functional layer is 0.60 μm.
[0202] Comparative Example 12
[0203] The difference between this comparative example and Example 1 is that the preparation parameter range of the B-DLC functional layer is adjusted so that the thickness of the B-DLC functional layer is 2.5 μm.
[0204] Comparative Example 13
[0205] The difference between this comparative example and Example 1 is that the preparation parameter range of the B-DLC functional layer is adjusted so that the mass percentage of B in the B-DLC functional layer is 8.0% and the mass percentage of C is 92.0%.
[0206] Comparative Example 14
[0207] The difference between this comparative example and Example 1 is that: x B y C z The preparation parameter range of the gradient transition layer makes Cr x B y C z The mass percentage of B in the gradient transition layer is 10%.
[0208] Test example
[0209] ①. The high temperature wear-resistant self-lubricating boron-doped diamond-like coatings prepared in Examples 2 to 14 were subjected to structural tests. The results showed that the B-DLC functional layers in the high temperature wear-resistant self-lubricating boron-doped diamond-like coatings prepared in the above examples all had a dense featureless structure, and the Cr base layer and the Cr x B y C z The gradient transition layers all show obvious columnar structures.
[0210] ②, A, the high temperature wear-resistant self-lubricating boron-doped diamond-like coating prepared in Example 1 was partially tested for performance, and the results are shown in Table 1 and Figure 2 shown. Figure 2 The friction coefficient curve and average friction coefficient value of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating prepared in Example 1 under different temperature atmospheres, wherein Ee is the area between the loading curve and the unloading curve, indicating the energy dissipated in the coating due to plastic deformation; Ep is the area under the unloading curve, indicating the elastic energy of the deformation. Figure 2 (a) corresponds to the result at room temperature (25°C), (b) corresponds to the result at 400°C, and (c) corresponds to the result at 500°C.
[0211] The hardness in Table 1 is measured with reference to GB / T 33051-2016 Determination of the thickness of the hardened layer of optical functional film surface hardening film; the equivalent elastic modulus E* is calculated according to the following formula: E* = E / (1-ν 2 ), where E refers to elastic modulus and ν refers to Poisson's ratio; hardness modulus ratio data are rounded off.
[0212] In addition, the same performance tests were performed on the coatings obtained in Examples 2 to 14 and Comparative Examples 1 to 14, and the results are also shown in Table 1.
[0213] B. The high-temperature wear-resistant self-lubricating boron-doped diamond-like coating prepared in Example 1 and the Al2O3 friction pair were subjected to friction tests at a room temperature (25°C) atmosphere and at high temperature atmospheres of 400°C and 500°C. The friction time of the friction tests under the conditions of 25°C, 400°C and 500°C was 900s. The results are shown in FIG. Figure 3 And as shown in Table 1. Figure 3 (a) corresponds to the result at 25°C, (b) corresponds to the result at 400°C, and (c) corresponds to the result at 500°C. Figure 3 It can also be seen that an easy-to-lubricate lamellar boron oxide-rich amorphous carbon transfer film is in situ formed at the wear scar, resulting in its excellent lubrication and friction reduction effect.
[0214] Furthermore, the same performance tests were performed on the coatings obtained in Examples 2 to 14 and Comparative Examples 1 to 14, and the results are also shown in Table 1.
[0215] Table 1 Performance results
[0216]
[0217] It can be seen from Table 1 that the high temperature wear-resistant self-lubricating boron-doped diamond-like coating provided by the embodiment of the present invention has high hardness, high toughness and low friction properties. In a wide temperature range from room temperature (25°C) to 500°C, especially in a high temperature atmospheric environment of 400-500°C, the coating exhibits excellent self-lubricating and wear-resistant properties.
[0218] In summary, the solution provided by the present invention has at least the following advantages:
[0219] (1) The high-temperature wear-resistant self-lubricating boron-doped diamond-like coating provided by the present invention has high hardness, high toughness and low friction characteristics. Compared with the traditional DLC coating, the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating provided by the present invention can effectively resist external wear and impact.
[0220] (2) The high-temperature wear-resistant self-lubricating boron-doped diamond-like coating provided by the present invention exhibits excellent self-lubricating and wear-resistant properties in a wide temperature range from room temperature (25°C) to 500°C, significantly improving the lubrication performance of the DLC coating in high-temperature atmospheres. In particular, in a high-temperature atmospheric environment of 400 to 500°C, the coating can form an easy-to-lubricate lamellar boron oxide-rich amorphous carbon transfer film in situ at the wear scar during friction, effectively reducing the friction coefficient.
[0221] (3) In terms of preparation method, the present invention innovatively combines DC magnetron sputtering technology with high-power pulse deposition technology assisted by an anode layer ion source. Compared with the traditional magnetron sputtering equipment in existing industrial production, the use of an ion source-assisted high-power pulse magnetron sputtering coating system for preparation improves the bombardment energy during the thin film deposition process, making it easier to prepare a hard nano-composite lubricating coating with special properties. At the same time, this preparation method has significant advantages such as low deposition temperature, high material utilization, low production cost, good coating uniformity, good preparation repeatability, and wide practicality.
[0222] (4) The high-temperature wear-resistant self-lubricating boron-doped diamond-like coating provided by the present invention can be widely used in the fields of high-temperature friction and wear protection of cutting tools, molds, high-tech equipment and their key components. The wear-resistant self-lubricating coating can be maturely applied in the range of 400 to 500°C to meet the lubrication and wear resistance requirements under harsh working conditions of high temperature atmosphere.
[0223] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A high temperature wear-resistant self-lubricating boron-doped diamond-like coating, characterized in that: The high-temperature wear-resistant self-lubricating boron-doped diamond-like coating comprises a Cr base layer, a Cr x B y C z Gradient transition layer and B-DLC functional layer; The Cr bottom layer has a columnar structure, and the thickness of the Cr bottom layer is 0.15 μm to 0.25 μm; x B y C z The gradient transition layer has a columnar structure. x B y C z The thickness of the gradient transition layer is 0.05 μm to 0.10 μm; the B-DLC functional layer has a dense featureless structure, and the thickness of the B-DLC functional layer is 0.8 μm to 2.0 μm; In the Cr base layer, the mass percentage of Cr is 99.5% to 99.99%; x B y C z In the gradient transition layer, the mass percentage of Cr is greater than 0 and does not exceed 99.99%, the mass percentage of B is greater than 0 and does not exceed 8%, and the remainder is C; in the B-DLC functional layer, the mass percentage of B is 3% to 5%, and the remainder is C.
2. The high temperature wear-resistant self-lubricating boron-doped diamond-like coating according to claim 1, characterized in that: Along the direction from close to the Cr base layer to away from the Cr base layer, the Cr x B y C z In the gradient transition layer, the mass percentage of Cr gradually decreases from 99.99% to 0%, and the mass percentage of B gradually increases from 0 to 8%.
3. The high temperature wear-resistant self-lubricating boron-doped diamond-like coating according to claim 1 or 2, characterized in that: The high temperature wear-resistant self-lubricating boron-doped diamond-like coating has at least one of the following characteristics: Feature 1: The hardness of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating is H, and the range of H is 20.0GPa to 25.0GPa; preferably 20.5GPa to 24.7GPa; Feature 2: The equivalent elastic modulus of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating is E*, and the range of E* is 185GPa to 245GPa, preferably 189.5GPa to 242.2GPa; Feature 3: The H / E* of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating is ≥ 0.1; preferably 0.102 to 0.108; Feature 4: The friction coefficient of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating in an atmospheric environment of 25°C is 0.090 to 0.100; preferably 0.090 to 0.098; Feature 5: The friction coefficient of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating in an atmospheric environment at 400°C is 0.050 to 0.055; Feature 6: The friction coefficient of the high-temperature wear-resistant self-lubricating boron-doped diamond-like coating in an atmospheric environment of 500°C is 0.040 to 0.050; Feature 7: The wear rate of the high temperature wear-resistant self-lubricating boron-doped diamond-like coating in an atmospheric environment of 25°C is no more than 3.50×10 -7 m 3 / N·m; feature 8: The wear rate of the high temperature wear-resistant self-lubricating boron-doped diamond-like coating in an atmospheric environment of 400°C is no more than 1.50×10 -6 m 3 / N·m; Feature 9: The wear rate of the high temperature wear-resistant self-lubricating boron-doped diamond-like coating in an atmospheric environment of 500°C is no more than 5.0×10 -6 m 3 / N·m; feature 10: The high temperature wear-resistant self-lubricating boron-doped diamond-like coating can form an easy-to-lubricate lamellar boron oxide-rich amorphous carbon transfer film in situ at the wear scar when rubbed at 400° C. to 500° C.
4. A method for preparing a high temperature wear-resistant self-lubricating boron-doped diamond-like coating according to any one of claims 1 to 3, characterized in that: The following steps are involved: Cr base layer, Cr x B y C z Gradient transition layer and B-DLC functional layer.
5. The preparation method according to claim 4, characterized in that: The Cr base layer is prepared by DC magnetron sputtering; The preparation conditions of the Cr bottom layer include: the vacuum degree in the equipment chamber is better than 1.0×10 -3 Pa, 120sccm~150sccm of argon gas is introduced into the equipment, and the gas pressure is maintained at 0.40Pa~0.45Pa; the substrate bias is -200V to -250V, and the bias duty cycle is 50%~60%; the target current is 1.0A~2.0A, and the deposition time is 5min~10min; the target material is a metal chromium target, in which the Cr content accounts for 99.5wt%~99.99wt%.
6. The preparation method according to claim 4, characterized in that: The Cr x B y C z Gradient transition layer; The Cr x B y C z The preparation conditions of the gradient transition layer include: introducing 120sccm to 150sccm of argon gas into the equipment and maintaining the gas pressure at 0.40Pa to 0.45Pa; the substrate bias is -200V to -250V, and the bias duty cycle is 50 to 60%; the target materials are metal chromium target and graphite-boron carbide composite target; the current of the metal chromium target is gradually reduced from 2.0A to 0A, and the current of the graphite-boron carbide composite target is gradually increased from 0A to 2.0A, and the deposition time is 8min to 12min.
7. The preparation method according to claim 4, characterized in that: The B-DLC functional layer is prepared by high-power pulsed magnetron sputtering technology assisted by an anode layer ion source; The preparation conditions of the B-DLC functional layer include: introducing 80sccm to 100sccm argon gas with a gas pressure of 0.25Pa to 0.30Pa; the substrate bias is -100V to -150V, and the bias duty cycle is 50% to 60%; a graphite-boron carbide composite target is used, and the B content in the graphite-boron carbide composite target is 5wt% to 10wt%; the HiPIMS pulse power is 2.0kW to 4.0kW, and the duty cycle is 1.0% to 3.0%; the anode layer ion source power is 0.18kW to 0.36kW, and the duty cycle is 50% to 60%; the deposition time is 4h to 6h.
8. The preparation method according to any one of claims 4 to 7, characterized in that: Before preparing the Cr base layer, the method further includes pre-treating the substrate; Preferably, the pretreatment includes grinding and polishing the substrate, then ultrasonic cleaning, placing the obtained substrate on a rotating rack in a vacuum chamber, and finally performing plasma glow cleaning using an anode layer ion source.
9. The preparation method according to claim 8, characterized in that: Ultrasonic cleaning time is 40min to 50min; And / or, the plasma glow cleaning comprises: fixing the substrate on a vacuum chamber rotating frame, and waiting for the vacuum degree to be better than 1.0×10 -3 Pa, introduce 150sccm~200sccm argon gas, maintain the gas pressure at 0.60Pa~0.80Pa; at the same time, adjust the substrate bias to -900V to -1000V, and the bias duty cycle is 50%~60%; then turn on the anode layer ion source, the anode layer ion source power is 0.18kW~0.36kW, the duty cycle is 50%~60%, and the plasma glow cleaning time is 10min~15min.
10. An application of the high temperature wear-resistant self-lubricating boron-doped diamond-like coating according to any one of claims 1 to 3, characterized in that: The high-temperature wear-resistant self-lubricating boron-doped diamond-like coating is used to prepare cutting tools, molds, high-tech equipment and key components thereof; Preferably, the tool comprises a milling cutter or a micro drill bit moving at high speed; Preferably, the die comprises a stamping die, a punch or an ejector pin surface; Preferably, the key components include planetary gears, sun gears or internal gear rings.
Citation Information
Patent Citations
Hydrogen-free diamond-like carbon film as well as preparation method and application thereof
CN109136843A
High-temperature super-lubricating silicon-doped diamond-like carbon film as well as preparation method and application thereof
CN116904925A
High-hardness wear-resistant DLC coating and preparation method thereof
CN117089819A
Low-friction high-wear-resistance solid lubricating coating and preparation method thereof
CN118241159A
Forming method of diamond-like carbon thin film and electrode material formed with the thin film on metal base board
JP2012188688A
Cited By
Sliding vane, manufacturing method thereof, compressor and refrigeration equipment
CN121408216A